Semiotika Ferdinand de Saussure dalam Cerpen "أم" Karya Mahmud Taymur - Luqman, Ahmad Luqman Hakim; Halim, Ahmad Luqman; Wahyuningsih, Irna Tri Wahyuningsih; Annisa, Nurul Fathia Annisa; Risna , Risna Risnawati; Wulandari, Wulandari Wulandari (Kitabina: Jurnal Bahasa dan Sastra, 2025)
This article discusses the semiotic study of Ferdinand De Saussure's theory in the short story "أم" in the Anthology of Short Stories "دنياجديدة" by Mahmud Taimur. The aim of this research is to analyze the signifiers and signifieds contained in the short story using the semiotic study of Ferdinand De Saussure, because this short story presents various characters, events, settings and complex story elements, and contains many implied meanings. This research uses descriptive qualitative methods, which is a type of research that uses methods to provide an overview of research results related to the phenomenon being studied. The data collection technique in this research is a content analysis technique, namely the researcher carries out the process of reading the short story text intensively, then the researcher carries out the data analysis process by classifying the main sentences related to semiotics in the short story "أم" by Mahmud Taimur, then the researcher describes the data and arranges it systematically. The results and discussion show that there are several signifiers and signifiers in the short story "أم" by Mahmud Taimur, namely that there are 71 signs that can be observed, so that a new, more complex meaning emerges.